The Influence of Digital Leadership and Digital Culture on Organizational Performance thru Techno-Work Engagement at the Immigration Office Class I Special Check Point Semarang - Marisa Efrilia; Viviorini; Gita Sugiyarti (Universitas 17 Agustus 1945 Semarang, 2026)
This study aims to analyze the influence of Digital Leadership and Digital Culture on Organizational Performance thru the mediation of Technowork Engagement at the Immigration Office Class I Special TPI Semarang. Digital transformation in public organizations requires a comprehensive understanding of leadership mechanisms, culture, and technology engagement in improving service performance. The research method uses a quantitative approach with Partial Least Squares-Structural Equation Modeling (PLS-SEM). Data was collected through a survey of 65 Immigration Office employees using a structured questionnaire. The research instrument has met the standards of validity and reliability. The analysis results show that Digital Leadership significantly influences Organizational Performance and Technowork Engagement. Digital Culture significantly influences Technowork Engagement but does not directly affect Organizational Performance. Technowork Engagement was proven to have a significant impact on Organizational Performance. The findings indicate that digital leadership is a crucial factor in the digital transformation of public organizations, while digital culture requires mediation through technological engagement to impact performance. The practical implications emphasize the importance of developing digital leadership capacity and strategies to enhance technowork engagement in optimizing the performance of immigration services.